2005
DOI: 10.1258/004947505774938611
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis in patients over the age of 50 years: 98 cases managed surgically

Abstract: Generalized peritonitis in patients over the age of 50 years is a common surgical emergency. This is a retrospective analysis of 98 cases managed surgically. Duodenal ulcer perforations, necrotizing enteritis, acute cholecystitis with perforation and small bowel perforations were the common causes. Most of them presented late, and many had associated conditions. Re-look laparotomies had a definite role to play. While there is significant decrease in the number of typhoid and tubercular peritonitis, there appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
3
1
0
Order By: Relevance
“…Respiratory complications are the known risk factors for the high mortality [32]. Relook laparotomies and intestinal stoma have a definite role to play in perforation peritonitis [33]; as seen in our study, 3.9 % patients went through redo surgery, intestinal stoma, and tension suturing. Factors contributing to redo surgery were persistent septicemia due to abdominal collection, interloop abscess, anastomosis leakage, and burst abdomen.…”
Section: Discussionsupporting
confidence: 58%
“…Respiratory complications are the known risk factors for the high mortality [32]. Relook laparotomies and intestinal stoma have a definite role to play in perforation peritonitis [33]; as seen in our study, 3.9 % patients went through redo surgery, intestinal stoma, and tension suturing. Factors contributing to redo surgery were persistent septicemia due to abdominal collection, interloop abscess, anastomosis leakage, and burst abdomen.…”
Section: Discussionsupporting
confidence: 58%
“…Factors contributing to the high mortality and postoperative complications are advanced age, late presentation, delay in the treatment, septicemia and associated co morbid, Respiratory complications are the known risk factors for the high mortality [ 32 ]. Re look laparotomies and abdominal washout had a definite role to play in perforation peritonitis [ 33 ], as seen in our study 37.3% patients go through redo surgery. Abdominal washout and tension suturing, factors contributing to redo surgery were persistent septicemia due to abdominal collection, inter loop abscess, anastomosis leakage and burst abdomen.…”
Section: Discussionsupporting
confidence: 52%
“…[19][20][21][22] Acid peptic disease was the second commonest cause of perforation requiring an early surgery for a favourable outcome. We found that in such cases the closure of perforation using a Graham's omental patch was a simple procedure with low mortality as supported by Subramanyam et al [23] Primary intestinal tuberculosis is common in developing countries like India as compared to the western countries. Extrapulmonary tuberculosis most commonly affects the ileocaecal region and the terminal ileum.…”
Section: Discussionsupporting
confidence: 53%